Thalidomide plus dexamethasone as initial therapy for multiple myeloma: overview of Mayo Clinic and Eastern Cooperative Oncology Group experience (Hematology Meeting Reports, 2009)
Dexamethasone has been shown to produce a response in at least 45% of patients who are newly diagnosed with multiple myeloma (MM) and in approximately one quarter of patients with relapsed or refractory disease.1,2A synergistic effect between dexamethasone and thalidomide has been identified, which is illustrated by the efficacy of this combination in relapsed MM.3 Studies of thalidomide and dexamethasone used to treat patients who are newly diagnosed with MM have yielded response rates from 64% to 72%.4,5 These results and others suggest that the combination of thalidomide and dexamethasone is an effective treatment choice for patients with MM.